Foreign infrastructure investment in developing countries: a dynamic panel data model of political risk impacts - Jiang, Weiling; Martek, Igor; Hosseini, M. Reza; Tamošaitienė, Jolanta; Chen, Chuan (Technological and Economic Development of Economy, 2019)
Foreign direct investment (FDI) is inhibited by political risk. Developing countries tend to experience higher levels of such risk, yet need foreign capital to generate growth. Moreover, foreign direct investment in infrastructure (FDII) – fundamental to economic growth – is particularly sensitive to political risk; characterized by high capital investment, longer investment periods, while especially exposed to mercurial shifts in government policy. Yet, no comprehensive study has been undertaken that measures the impact of political risk on FDII in developing countries. This paper addresses this lack. Twelve political risk indicators, drawn from the International Country Risk Guide Index, are used to quantify the political risk inherent to 90 developing countries, over the period 2006 to 2015. An Arellano-Bond GMM estimator is developed which measures the dollar value impact of risk on both FDI and FDII. A comparison of results confirms that FDII is generally more sensitive to risk than is FDI, however the influence of risk categories is found to vary significantly. The findings can be expected to inform infrastructure policy-makers and foreign investors alike on the dollar-impact of determinable risk levels on foreign-funded projects, and in so doing better facilitate corrective risk mitigation strategies.